KELAYAKAN MULTIMEDIA INTERAKTIF BERBASIS ANDROID PADA MATERI FUNGI KELAS X SMA - Nanda Zakiyyatulmuna; Kurnia Ningsih; Eko Sri Wahyuni (Bioilmi: Jurnal Pendidikan, 2022)
The analysis results of the needs teachers and students at Pontianak Mujahidin High School, the results obtained were that the fungi is the material with lowest average compare to other materials, students prefer learning media that combines text, images and video as well as students use android smartphones so it is necessary to do research on the feasibility of android-based interactive multimedia on fungi material. This study aims to produce android-based interactive multimedia, test the feasibility of interactive multimedia and see student responses to android-based interactive multimedia on functions material. The research method used is R&D (Research & Development) with the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). Response trials were carried out on 12 students of Pontianak Mujahidin High School. The validation calculation in this study uses the Aiken V formula with 6 validators and 4 rating ratings. The results of the assessment of media and material experts obtained a value of Vcount>Vtable (0.87>0.78) so that learning media can be said to be valid and feasible to use. The results of the response trial in this study were 83.74% with a very strong category, so Android-based interactive multimedia on class X high school functions is very suitable for use in the learning process at school.